2021
DOI: 10.1038/s42003-021-02382-w
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of neurovascular coupling dynamics along vascular arbors in layer II/III somatosensory cortex

Abstract: The spatial-temporal sequence of cerebral blood flow (CBF), cerebral blood volume (CBV) and blood velocity changes triggered by neuronal activation is critical for understanding functional brain imaging. This sequence follows a stereotypic pattern of changes across different zones of the vasculature in the olfactory bulb, the first relay of olfaction. However, in the cerebral cortex, where most human brain mapping studies are performed, the timing of activity evoked vascular events remains controversial. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 55 publications
2
31
1
Order By: Relevance
“…In alpha-chloralose anaesthetized somatosensory cortex, Hall and colleagues found response frequency decreased as branching order increased (i.e., capillaries responded less frequently than arterioles; Hall et al, 2014 ), though first and second branch order capillaries showed larger and faster dilations than arterioles, a finding subsequently supported by other studies ( Zhang et al, 2021 ). In the olfactory bulb, the region around the branch off the arteriole also dilated first, with slower responses up and downstream ( Rungta et al, 2021 ). However, the same group found much more variable timings in neocortex of ketamine-medetomidine anaesthetized or awake mice, with capillaries or arterioles each being faster on some occasions ( Rungta et al, 2021 ), and in both these reports, mid-capillary dilations were very small (though these data conflate responders and non-responders, unlike some other studies, Hall et al, 2014 ; Shaw et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alpha-chloralose anaesthetized somatosensory cortex, Hall and colleagues found response frequency decreased as branching order increased (i.e., capillaries responded less frequently than arterioles; Hall et al, 2014 ), though first and second branch order capillaries showed larger and faster dilations than arterioles, a finding subsequently supported by other studies ( Zhang et al, 2021 ). In the olfactory bulb, the region around the branch off the arteriole also dilated first, with slower responses up and downstream ( Rungta et al, 2021 ). However, the same group found much more variable timings in neocortex of ketamine-medetomidine anaesthetized or awake mice, with capillaries or arterioles each being faster on some occasions ( Rungta et al, 2021 ), and in both these reports, mid-capillary dilations were very small (though these data conflate responders and non-responders, unlike some other studies, Hall et al, 2014 ; Shaw et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the olfactory bulb, the region around the branch off the arteriole also dilated first, with slower responses up and downstream ( Rungta et al, 2021 ). However, the same group found much more variable timings in neocortex of ketamine-medetomidine anaesthetized or awake mice, with capillaries or arterioles each being faster on some occasions ( Rungta et al, 2021 ), and in both these reports, mid-capillary dilations were very small (though these data conflate responders and non-responders, unlike some other studies, Hall et al, 2014 ; Shaw et al, 2021 ). Precapillary sphincters, where studied, have often shown larger dilations, as a proportion of their diameter, than adjacent arterioles and capillaries ( Grubb et al, 2020 ; Zambach et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next to the degree and speed of neurovascular reactivity in different vascular beds, our data also shed some light on the signal transduction occurring along the vascular tree during NVC. A recent study from Rungta et al showed that following neuronal stimulation blood velocity increases first in the surrounding capillary bed and only somewhat later in penetrating and pial arterioles ( 69 ), suggesting that capillaries trigger signals which are transferred to upstream arterioles and recruit them to the coupling response. Consequently, if the capillary response to neuronal activation is disturbed, also the upstream response should be reduced or interrupted.…”
Section: Discussionmentioning
confidence: 99%
“…As our study shows that the amount and timing of locomotion (relative to whisker stimulation) can impact the amplitude of an evoked haemodynamic response we suggest that, where possible, groups should monitor locomotion in their awake imaging experiments – particularly when using sensory stimulation. If locomotion behaviours cannot be monitored, other methods could be used to limit locomotion behaviours, such as training animals to remain stationary 32 . Monitoring locomotion is especially important to consider when comparing different disease groups, in which locomotion may differ 33 – if locomotion behaviour is not monitored (or excluded), confounded conclusions could potentially be made.…”
Section: Discussionmentioning
confidence: 99%